PENINGKATAN KREATIVITAS MATEMATIKA MATERI KUBUS MELALUI PENDEKATAN KONTEKSTUAL DI KELAS V SEKOLAH DASAR - Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
The aims of this study were: To increase the mathematical creativity of cube material through a contextual approach in fifth grade of elementary school. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of action, observation and reflection. The research subjects were fifth grade elementary school students. Data collection techniques using observation, interviews, and documentation. There is an increase in student creativity as indicated by an increase in student attitudes when participating in learning in each cycle. In cycle I with a percentage of 66.5% including sufficient criteria. In cycle II, a percentage of 84.5% was obtained with good creativity criteria. contextual can increase the creativity of mathematical cube material through a contextual approach in class V elementary school.